(untitled) (Vietnam Journal of Community Medicine, 2024)
Introduction: Hypogonadism is a common abnormality in HIV-infected men (Human Immunodeficiency Virus) and can have implication for sexual function and body metabolism. However, this condition often remains silent, underdiagnosed, and inadequately treated. Case Report: We report a case of a 28-year-old male patient diagnosed with HIV infection 5 years ago, continuously treated with antiretroviral drugs (ARVs) with a good response. The patient presented with symptoms of decreased libido, erectile dysfunction, and difficulty ejaculating in the past 2 years. Clinical examination revealed a slightly feminine physique, with both testes showing mild reduction in size. Laboratory tests indicated severely decreased levels of testosterone, FSH, and LH. The patient was treated with transdermal testosterone daily and Tadalafil on-demand. After 3 months of treatment, there was a significant improvement in symptoms, clinical manifestations, and endocrine parameters. Conclusion: Early screening for hypogonadism in HIV-infected male individuals and the use of testosterone therapy can improve the quality of life for these patients.